2020
DOI: 10.1111/1742-6723.13552
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between triage streamed treatment location and time to appropriate antibiotics in emergency department patients with septic shock

Abstract: Objective: Early recognition and treatment for sepsis is critical in improving patient outcomes. The present study sought to examine whether triage location was associated with time to appropriate antibiotics in a cohort of ED patients with septic shock. Methods: Septic shock patients were identified from a database of ED patients admitted with infection. Demographic, clinical and outcome data were reported by triage location. Time to event analyses sought to identify the association between triage location an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
4
0
2
Order By: Relevance
“…Ceftriaxone and gentamicin were frequency underdosed, which is consistent with results from other studies 14–16 . Other indices of appropriate investigations and therapy such as blood culture collection rates were mostly consistent with established guidelines 17 and previous studies 12,18–20 . Most patients had a serum lactate measured.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Ceftriaxone and gentamicin were frequency underdosed, which is consistent with results from other studies 14–16 . Other indices of appropriate investigations and therapy such as blood culture collection rates were mostly consistent with established guidelines 17 and previous studies 12,18–20 . Most patients had a serum lactate measured.…”
Section: Discussionsupporting
confidence: 88%
“…[14][15][16] Other indices of appropriate investigations and therapy such as blood culture collection rates were mostly consistent with established guidelines 17 and previous studies. 12,[18][19][20] Most patients had a serum lactate measured. In-hospital mortality rates were also consistent with previous studies in Australian hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also showed that the time for antibiotic administration was shorter in patients classified as having higher priority, when compared to the others ( 26 - 27 ) . Furthermore, patient classification for lower priorities of care has been shown to be an independent risk factor for delay in administering the first dose of antibiotic ( 28 ) .…”
Section: Discussionmentioning
confidence: 87%
“…A study in 2015, conducted prior to the introduction of the sepsis 3 definition, noted that the Australasian Triage Scale system only leads to moderate accuracy and moderate agreement between nurses regarding sepsis identification 21 . Furthermore, patients triaged to lower acuity treatment areas face a significant delay to antibiotic treatment 23 . Therefore, this may be an area to focus quality improvement and nurse education strategies.…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, patients triaged to lower acuity treatment areas face a significant delay to antibiotic treatment. 23 Therefore, this may be an area to focus quality improvement and nurse education strategies. A qualitative study exploring ED nurse perceptions and experience recognising sepsis in an Australian ED also highlighted the important role nurses have with regards to sepsis recognition, particularly at triage.…”
Section: Discussionmentioning
confidence: 99%